Citrus Tree Stresses: Effects on Growth and Yield - James Syvertsen; Edward A. Hanlon (EDIS)
HS-1138, a 6-page illustrated fact sheet by J. Syvertsen and E.A. Hanlon, provides information dealing with citrus responses to environmental conditions for professionals involved with citrus management practices. It explains how citrus trees respond to changes in availability of water and nutrients; discusses plant-stress situations and their effects on citrus growth and productivity; and discusses the balance between roots and shoots. Includes references. Published by the UF Department of Horticultural Sciences, May 2008.